(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2017)
A building is supposed to be designed suitable for the community’s life. The emergence of multistoreyed building as a solution over limited usable land has caused the practice of International Style where a building no longer regards the characteristics of place where they are built. According to the theory of Critical Regionalism, there should be appropriate integration between local and contemporary factors. Bali as one of many region in Indonesia with abundance of culture is seen as a suitable place to applicate this theory. The type of multistoreyed building chosen was apartment, which is becoming a prevalent phenomenon in the mentioned region, and also as a settlement building type it is seen as the closest type to inhabitant’s activity thus has a close connection with the community’s culture. The research is made to discover how far has the local and contemporary factors been applied to apartments build in Bali according to the theory of Critical Regionalism. This research utilizes qualitative method through the use of Critical Regionalism principles from Ken Yeang in the form of Functional Connection to analyze the case study. There are four steps of said principle, Direct Connection, Indirect Connection, Inclusive Contemporary Connection, and Landscape Connection. At the result of this research, it was found that there was a lack in application of Critical Regionalism principles particularly in principles of building form, the usage of traditional concepts, facilities availability, and treatment towards environtment.